Situation Report: Bulgaria, 14 April 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov in Austria Foreign Minister Bashev in Moscow Zhivkov's Letter to the Academy of Fine Arts New Civil Rituals Decreed in Bulgaria Soviet Cosmonaut in Sofia Trade Union Activities